An Overview of Antimicrobial Compounds from African Edible Insects and Their Associated Microbiota - Cynthia M. Mudalungu; Chrysantus M. Tanga; Segenet Kelemu; Baldwyn Torto (MDPI AG, 2021)
The need for easily biodegradable and less toxic chemicals in drug development and pest control continues to fuel the exploration and discovery of new natural molecules. Like certain plants, some insects can also respond rapidly to microbial infections by producing a plethora of immune-induced molecules that include antibacterial and antifungal peptides/polypeptides (AMPs), among other structurally diverse small molecules. The recent recognition that new natural product-derived scaffolds are urgently needed to tackle life-threatening pathogenic infections has been prompted by the health threats posed by multidrug resistance. Although many researchers have concentrated on the discovery of AMPs, surprisingly, edible insect-produced AMPs/small molecules have received little attention. This review will discuss the recent advances in the identification and bioactivity analysis of insect AMPs, with a focus on small molecules associated with the microbiota of selected African edible insects. These molecules could be used as templates for developing next-generation drugs to combat multidrug-resistant pathogens.